Pengaruh Literasi Digital Masyarakat terhadap Efektivitas Partisipasi Publik dalam Governansi Digital (International Forum of Researchers and Lecturers, 2023)
This study examines the relationship between the level of digital literacy of the community and the effectiveness of public participation in the digital governance process. Using a quantitative approach through a structured survey of 450 respondents in three major cities in Indonesia, this study analyzes how digital literacy skills affect community involvement in digital government platforms, public policy making, and e-participation mechanisms. The results of the study show a significant positive correlation (r=0.742, p<0.001) between digital literacy and the level of participation in digital governance. Communities with high digital literacy showed 3.2 times more active participation in online public consultations, provided better quality policy feedback, and used e-government services more optimally. These findings provide theoretical contributions to the understanding of digital citizenship and provide practical recommendations for the development of inclusive digital governance strategies.